Usefulness of 3D CT in Diagnosis of Cervical Rib Presenting as Supraclavicular Swelling of Short Duration - Shruti Chandak; Ashutosh Kumar (Journal of Clinical and Diagnostic Research, 2014)
This is a unique case of cervical rib since the patient presented as a firm neck swelling of short duration which was clinically palpable as a superficial neck mass and referred for FNAC for the same. Since FNAC did not yield any positive result, the patient was then referred for CT which showed bilateral cervical ribs with pseudoarticulation with the 1st thoracic rib on the right side which is quite rare. The clinical importance of our case is to keep in mind a differential diagnosis of cervical rib in firm to hard clinically palpable posterior triangle neck masses. It is also important to diagnose cervical ribs in patients undergoing CT of the neck since they are under reported as determined in previous studies.